Impact of School Feeding Programs on Student Attendance and Performance in Ghana - Appiah, Kwesi (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the impact of school feeding programs on student attendance and performance in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: School feeding programs in Ghana significantly boost student attendance and academic performance, particularly benefiting girls and children in rural areas. These programs reduce hunger, improve nutrition, and increase engagement, leading to enhanced educational outcomes and lower dropout rates. Unique Contribution to Theory, Practice and Policy: Maslow's hierarchy of needs theory, social cognitive theory & expectancy-value theory may be used to anchor future studies on the impact of school feeding programs on student attendance and performance in Ghana. Implement robust monitoring and evaluation frameworks to assess the effectiveness of feeding programs regularly. Integrate school feeding programs into national educational policies as a fundamental component of the educational framework.